PAKPAK LANGUAGE TRANSLATOR APPLICATION INTO INDONESIAN USING ALGORITHM BOYER MOORE BASED ON ANDROID - Khairani Purba; Charles Jhony Mantho Sianturi; Mikha Dayan Sinaga; Nita Sari Sembiring; Erwing Ginting; Muhammad Fauzi (Jurnal Riset Informatika, 2021)
The lack of preservation is also the knowledge of the Pakpak Language in Indonesia, which causes the Pakpak Language to be less preserved, especially for young people who continue to keep abreast of the times. This causes the process of globalization and urbanization which causes assimilation and acculturation, especially in urban areas. This situation triggers a new language that is very popular, especially for young people who unconsciously, it makes us lose our identity as a society that has tribes and customs each – and the emergence of international and national schools that require students to speak foreign languages. Therefore, learning is needed to preserve Pakpak Language. By making a Pakpak to Indonesian translator application that uses the Android Based Boyer Moore algorithm. This translator application was made for the introduction of the PakpakLangugae to the wider community so that the sustainability of the Pakpak Language is maintained and this translator application can translate the Pakpak Language into Indonesian or vice versa based on the prevailing Pakpak – Indonesian dictionary.